NURSING RESEARCH DEVELOPMENT: ANALYSIS STUDY - Cianelli, Rosina; Urrutia, María Teresa; Ferrer, Lilian; Poupin, Lauren; Masalán, Patricia; Villegas, Natalia; Arratia, Alejandrina; Ferrer, Ximena (Investigación y Educación en Enfermería, 2009)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective: to present the areas of research in the School of Nursing at the Pontificia Universidad Catolica de Chile between 2001 and 2004, as well as presenting a new proposal for increased impulse in nursing research. Methodology: development was carried out in four phases: I. Evaluation of current scientific production through the revision of the organization’s annual plans; II. Analysis of information provided by key informants; III Literature review andgroup work with academics from the organization; IV. Triangulation of information. Results: sixty per cent of the scientific production in the School of Nursing at the Pontificia Universidad Católica de Chile between 2001 and 2004 could not be organized within the determined areas or lines of research for those years. Diverse proposals were elaborated in order to allow academics to incorporate themselves into the new areas of research avoiding dispersion and centralizing common strengths among existing projects. After the triangulation of information, three new areas of research were created: 1. Formation of human resources in health, 2. Nursing Care Management and 3. Strengthening of clinical nursing. Conclusions: it is suggestedthat researchers from the SON-UC orient their work towards those areas identified, which will contribute to strengthening research and improving both internal and external visibility of the academic entity; attracting new resources for research.